The Preparation Faults Manifesting As Finish Line Defects - A. H. Mohamed, Khadiga (Libyan Journal of Dentistry, 2017)
This study was done to evaluate different finish line defects due to fault preparation, In addition to that to determination of their locations (upper, lower, anterior, posterior). Methods: 175 working casts with different finish line defects (common errors and mistakes happens in the finish line) were collected from various dental laboratories in Benghazi. The working casts were classified to five groups according to the type of the finish line defect. group (1): Unidentifiable or light finish line, group (2): The finish line Not continuous, group (3): Double or several finish lines, group (4): Rough finish line and group( 5): Nodules on finish line. The collected data have analyzed statically. Each group subdivided into two divisions (upper, lower) then each division divided into three subgroups (Anterior, premolar, Molar) according to position of tooth in the arch. Results: The percentage for incidence of each group were as follow Group (1) = 30% mostly in lower molars and upper premolars (40.4%, 32.7%) respectively. Group (2) =24% the highest percentage in lower molar (33.3%). Group (3) =16% the highest was 39.3% of them occur in lower molars also. Group (4) = 22% with (35.9%, 23.1%) in lower molars and upper molars respectively. Group (5) = 8% mostly in lower molars (35.7%). independent-samples t-test was conducted which revealed lower molars are the most significant for all the subdivisions (M13, SD5.8) t(4)=5, p=0.07 Conclusion: The careful inspection of the finish line on the working cast is an essential critical step for obtaining a restoration with an accurate marginal integrity .